2003
DOI: 10.1097/01.sla.0000089853.11184.53
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation Under a Tolerogenic Regimen of Recipient Pretreatment and Low-Dose Postoperative Immunosuppression With Subsequent Weaning

Abstract: With this approach to immunosuppression, it has been possible to avoid early posttransplant overimmunosuppression and thereby to promote the evolution of a degree of partial tolerance sufficient to undertake substantial dose reduction. The strategy, which is applicable for all organ grafts, constitutes a paradigm shift in transplant management at our center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 12 publications
0
57
1
1
Order By: Relevance
“…In clinical transplantation, the possible tolerogenic effect of anti-T-cell antibodies may be inhibited by concomitant long-term immunosuppression. Recently, Starzl et al [25,26] demonstrated an excellent short-term outcome with an extremely low need for systemic immunosuppressants in various organ recipients pre-treated with rabbit polyclonal T cell antibodies. In the intervention study with humanized non-Fc receptor binding anti-CD3 antibodies, Herold et al observed an inverted CD4 + /CD8 + cell ratio 3 months following drug administration [22] which may support the concept of a durable tolerogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical transplantation, the possible tolerogenic effect of anti-T-cell antibodies may be inhibited by concomitant long-term immunosuppression. Recently, Starzl et al [25,26] demonstrated an excellent short-term outcome with an extremely low need for systemic immunosuppressants in various organ recipients pre-treated with rabbit polyclonal T cell antibodies. In the intervention study with humanized non-Fc receptor binding anti-CD3 antibodies, Herold et al observed an inverted CD4 + /CD8 + cell ratio 3 months following drug administration [22] which may support the concept of a durable tolerogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their early minimization of immunosuppressive therapy, neither patient MM nor CA underwent an acute rejection episode during the 3-y followup period. Shapiro et al's study (14) remains a benchmark trial of minimized tacrolimus monotherapy in renal transplant recipients: In this study, 150 patients were treated with 5 mg/ kg antithymocyte globulin with bolus prednisone as induction and were subsequently treated with tacrolimus monotherapy. Under this regimen, 37% of patients underwent acute rejection by 4 mo.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline CAN scores averaged from 1.3 to 2.0 to 2.6 in the three successively compiled series. The acceptance of kidneys with an increasing incidence and severity of preexisting 18 6 17 40 9 16 donor disease reflected nationwide efforts to expand the organ pool, ie, by relaxing the criteria for organ acceptance.…”
Section: Chronic Allograft Nephropathymentioning
confidence: 99%